Comparative Study of Lateral Internal Sphincterotomy versus Local 0.4% Glyceryl Trinitrate Ointment for the Treatment of Chronic Anal Fissure - Utban Ali Shah; Tabish Iqbal; Khurram Sarafaraz; Muhammad Idress; Momina Javed; Jawad Hamed (Journal of Bahria University Medical and Dental College, 2024)
Objectives: To compare the outcomes of “Lateral Internal Sphincterotomy (LIS)” versus local “0.4% Glyceryl Trinitrate (GTN)” ointment for the treatment of chronic anal fissure.